2020
DOI: 10.3389/fimmu.2020.603050
|View full text |Cite
|
Sign up to set email alerts
|

IgE and IgG Antibodies as Regulators of Mast Cell and Basophil Functions in Food Allergy

Abstract: Food allergy is a major health issue, affecting the lives of 8% of U.S. children and their families. There is an urgent need to identify the environmental and endogenous signals that induce and sustain allergic responses to ingested allergens. Acute reactions to foods are triggered by the activation of mast cells and basophils, both of which release inflammatory mediators that lead to a range of clinical manifestations, including gastrointestinal, cutaneous, and respiratory reactions as well as systemic anaphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 213 publications
2
82
0
4
Order By: Relevance
“… 144–146 These may represent food exposures in patients with impaired barriers as opposed to immunologic reactions contributing to symptoms, as resolution of food allergies is generally associated with development of increased food-specific IgG and IgG4 levels. 147 , 148 On the contrary, several studies have shown improvement in symptoms on elimination diets based on food-specific IgG testing with a prompt decrease in food-specific IgG in one study. 145 , 149 , 150 …”
Section: Treatmentmentioning
confidence: 94%
“… 144–146 These may represent food exposures in patients with impaired barriers as opposed to immunologic reactions contributing to symptoms, as resolution of food allergies is generally associated with development of increased food-specific IgG and IgG4 levels. 147 , 148 On the contrary, several studies have shown improvement in symptoms on elimination diets based on food-specific IgG testing with a prompt decrease in food-specific IgG in one study. 145 , 149 , 150 …”
Section: Treatmentmentioning
confidence: 94%
“…Besides FceR1/IgE, multiple other stimuli activate mast cells and can induce differential release granule and non-granule mediators from mast cells (72)(73)(74)(75). Furthermore, basophil mediators may also be involved in anaphylaxis as the FcεR1 receptor is also expressed on basophils (68).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, AIT induces a pro-tolerogenic state, promoting allergen-specific IgG/IgG4 production opposed to sIgE by B cells (15). IgG and IgG4 not only selectively compete with IgE in allergen binding, but also the engagement of the FcgRIIb receptor by allergen-IgG complexes cross-linking with surface IgE-FcϵRI actively inhibits MC activation (218,(239)(240)(241)(242). IgG-mediated inhibition also prevents further amplification of IgE production, by reducing Th2 cytokine release from activated MCs and basophils (242).…”
Section: Modulation Of Mast Cell Reactivity Using Allergen-specific Immunotherapymentioning
confidence: 99%